A surface lanthanum modified high-nickel ternary positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202210590519.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-05-26
AI Technical Summary
气相化学工艺(如化学气相沉积法)虽然可以实现精确的纳米薄膜沉积,但其存在产率低、技术复杂和有毒性等缺点
[0039]本发明从包覆物种的选择和控制出发,立足于低成本、高效的表面处理工艺,进一步结合后期的高温热处理过程,调控表面包覆物种与高镍正极在表面上的化学反应,实现高镍正极表面物理化学性能的调控与优化,以此获得高稳定的正极/电解液界面,这对于提升高比能量锂离子电池的稳定性和安全性具有重要的理论和应用价值。具体而言:
Smart Images

Figure CN117174901B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology and relates to a high-stability, high-nickel ternary cathode material modified with lanthanum on its surface, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have become the primary power source for portable electronic devices and electric vehicles due to their high energy density, high operating voltage, good safety, and lack of memory effect. Currently, with the continuous upgrading of these products, increasingly higher demands are being placed on lithium-ion batteries, which are developing towards higher energy density and better safety.
[0003] Cathode materials, as one of the core components of lithium-ion batteries, play a crucial role in the overall performance of the battery. Among them, high-nickel ternary layered oxides are considered the most promising cathode materials for next-generation high-energy-density lithium-ion batteries due to their high specific capacity and high discharge voltage. However, the introduction of high-energy-density cathode materials is often accompanied by more severe surface side reactions, thus bringing greater safety risks. In this context, starting from the control of the surface and interface structure of cathode materials, and based on the control of surface chemical properties, obtaining a highly stable cathode / electrolyte interface has become an important means to improve battery stability. Surface treatment of high-energy-density cathode materials to improve surface stability and effectively suppress side reactions between high-energy-density cathodes and organic electrolytes has become an important strategy and reliable approach for the control of the cathode material surface and interface.
[0004] However, the design and implementation of nanoscale surface layers is both a key focus and a challenge in the control of the surface structure of cathode materials. On the one hand, most inert coatings have poor electronic and ionic conductivity, which often increases the charge transfer resistance between the cathode and electrolyte interface, leading to polarization and capacity loss during charging and discharging. Therefore, it is urgent to design and control the coating state by combining the inherent properties of the surface coating species to optimize performance such as interfacial ion transport capacity and side reaction suppression. On the other hand, current surface coating processes often rely on solid-phase mixing methods, which can rapidly introduce modified species onto the cathode material surface, but it is difficult to effectively control the state of the coated species on the cathode material surface. Therefore, there are challenges in the control and optimization of the protective effect. Although vapor-phase chemical processes (such as chemical vapor deposition) can achieve precise nanofilm deposition, they have drawbacks such as low yield, technical complexity, and toxicity. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a lanthanum-modified high-nickel ternary cathode material, its preparation method, and its applications, thereby improving the stability and safety of existing high-nickel ternary cathode materials. Furthermore, given the inherent sensitivity of high-nickel ternary cathode materials to water and air, structural degradation often occurs during surface treatment due to environmental exposure, affecting application performance. The surface treatment process of this invention, while ensuring no additional damage to the high-nickel ternary cathode material, can fully meet the needs of scale-up production, offering advantages such as low cost and high reliability.
[0006] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution:
[0007] The present invention provides a cathode material, the cathode material comprising a high-nickel ternary cathode material and a lithium lanthanate nano-modification layer formed by lanthanum modification on the surface of the high-nickel ternary cathode material.
[0008] Among them, lithium lanthanum oxide nano-modification layer can be used as a lithium-ion conductor coating.
[0009] According to an embodiment of the present invention, the mass fraction of lanthanum in the cathode material is 0.1% to 2%, exemplarily 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, and 2.0%.
[0010] According to an embodiment of the present invention, the high-nickel ternary cathode material has the structural formula LiNi. x Co y Mn 1-x-y O2, where:
[0011] 0.6 ≤ x < 1, for example, x = 0.6, 0.7, 0.8, 0.91;
[0012] 0 < y ≤ 0.2, for example, y = 0.06, 0.1, 0.2;
[0013] x+y<1.
[0014] According to an exemplary embodiment of the present invention, the high-nickel ternary cathode material can be LiNi. 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.91 Co 0.06 Mn 0.03 O2.
[0015] According to an embodiment of the present invention, the high-nickel ternary cathode material includes single-crystal and polycrystalline high-nickel ternary cathode materials.
[0016] This invention also provides a method for preparing the above-mentioned cathode material, comprising the following steps:
[0017] (1) Dissolve the soluble lanthanum salt and precipitant in a non-aqueous solvent and stir to obtain solution A;
[0018] (2) Add the high-nickel ternary cathode material to solution A and disperse it to obtain suspension B;
[0019] (3) Heating suspension B (to promote chemical reaction and introduce lanthanum element in solution to the surface of cathode material), then centrifuging, washing and drying the reaction product to obtain surface-modified high-nickel ternary cathode material;
[0020] (4) The surface-modified high-nickel ternary cathode material prepared in step (3) is calcined at high temperature in an oxygen atmosphere to obtain a surface-modified high-nickel ternary cathode material with lanthanum species.
[0021] According to an embodiment of the present invention, in step (1), the soluble lanthanum salt includes, but is not limited to, a soluble metallic lanthanum salt containing metallic lanthanum, such as at least one selected from lanthanum nitrate, lanthanum sulfate, lanthanum carbonate, lanthanum chloride, lanthanum acetate, lanthanum acetylacetone, lanthanum isopropoxide, lanthanum ethoxylate, and lanthanum oxalate.
[0022] According to an embodiment of the present invention, in step (1), the precipitant is an organic or inorganic reagent containing nitrogen, such as at least one selected from formamide, acetamide, triethanolamine, ammonium formate, ammonium acetate, ammonium propionate, ammonium carbonate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, hexamethylenetetramine, urea, and ammonia.
[0023] According to an embodiment of the present invention, in step (1), the non-aqueous solvent is selected from at least one of anhydrous organic alcohols and / or ketone solvents, for example, it can be selected from at least one of anhydrous methanol, ethanol, isopropanol, n-propanol, ethylene glycol, n-butanol, acetone, etc., preferably anhydrous ethanol.
[0024] Furthermore, the non-aqueous solvent used in this invention is of chromatographic purity and has a water content ≤0.1wt%.
[0025] According to an embodiment of the present invention, in step (1), the concentration of the soluble lanthanum salt is 1 × 10⁻⁶. -5 ~0.1 mol / L, preferably 1×10 -4 ~0.01mol / L, exemplary value is 1×10 -5 mol / L, 1×10 -4 mol / L, 1×10 -3 mol / L, 0.01mol / L, 0.1mol / L.
[0026] According to an embodiment of the present invention, in step (1), the concentration of the precipitant is 1×10⁻⁶. -5 ~0.3 mol / L, more preferably 3×10 -4 ~0.03mol / L, exemplary value is 1×10 -5 mol / L, 1×10 -4 mol / L, 3×10 -4 mol / L, 1×10 -3 mol / L, 0.01mol / L, 0.03mol / L, 0.1mol / L, 0.3mol / L.
[0027] According to an embodiment of the present invention, the mass ratio of the high-nickel ternary cathode material to the soluble lanthanum salt is 300-5, preferably 150-20, and exemplary ratios are 300, 200, 150, 75, 38, 20, 10, and 5.
[0028] According to an embodiment of the present invention, in step (2), the high-nickel ternary cathode material has the definition and selection as described above.
[0029] According to an embodiment of the present invention, in step (3), the reaction temperature is 5 to 150°C, preferably 60 to 80°C, and exemplarily 5°C, 20°C, 40°C, 60°C, 80°C, 100°C, and 150°C.
[0030] According to an embodiment of the present invention, in step (3), the reaction time is 0.5 to 48 hours, preferably 2 to 6 hours, and exemplarily 0.5 hours, 3 hours, 6 hours, 8 hours, 12 hours, 24 hours, and 48 hours.
[0031] According to an embodiment of the present invention, in step (4), the calcination temperature is 300-1000℃, preferably 600-800℃, and exemplarily 300℃, 400℃, 600℃, 700℃, 800℃, and 1000℃.
[0032] According to an embodiment of the present invention, in step (4), the calcination time is 0.5 to 24 hours, preferably 1 to 5 hours, and exemplarily 0.5 hours, 1 hour, 3 hours, 5 hours, 8 hours, 12 hours, 24 hours, and 48 hours.
[0033] According to an embodiment of the present invention, in step (4), the heating rate of calcination is 1 to 10 °C / min, for example 1 °C / min, 5 °C / min, or 10 °C / min.
[0034] The present invention also provides the application of the above-mentioned cathode material in lithium-ion batteries.
[0035] The present invention also provides a lithium-ion battery containing the above-mentioned positive electrode material.
[0036] According to an embodiment of the present invention, the positive electrode of the battery further includes a conductive agent Super-P and a binder polyvinylidene fluoride (PVDF).
[0037] According to an embodiment of the present invention, in the positive electrode, the mass ratio of the positive electrode material to the conductive agent and the binder is (8-0):(1-9):1, for example 8:1:1.
[0038] The beneficial effects of this invention:
[0039] This invention starts with the selection and control of coating species, focusing on low-cost and efficient surface treatment processes. It further combines this with subsequent high-temperature heat treatment to regulate the chemical reaction between the surface-coated species and the high-nickel cathode, thereby controlling and optimizing the physicochemical properties of the high-nickel cathode surface. This results in a highly stable cathode / electrolyte interface, which has significant theoretical and practical value for improving the stability and safety of high-energy-density lithium-ion batteries. Specifically:
[0040] (1) This invention provides a method for preparing surface-modified lanthanum-modified high-nickel ternary cathode materials, which has the advantages of simple process, low cost, environmental friendliness, and large-scale production capability. This method utilizes a reaction environment provided by a non-aqueous solvent, effectively avoiding damage to the high-nickel ternary cathode material from ambient water while introducing lanthanum species onto the cathode material surface. Furthermore, high-temperature treatment yields surface-modified lanthanum-modified cathode materials with structural stability, achieving surface modification of the cathode material and thus obtaining excellent electrochemical performance.
[0041] (2) The high-nickel ternary cathode material of the present invention, through surface coating and subsequent high-temperature treatment, achieves surface modification and stabilization of lanthanum species, exhibiting better electrochemical stability during battery testing. Simultaneously, the surface modification method of the cathode material of the present invention can improve the structural stability of the cathode material, thereby improving the cycle performance of the battery. Attached Figure Description
[0042] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the lanthanum-modified high-nickel ternary single-crystal cathode material in Example 1.
[0043] Figure 2 This is a scanning electron microscope (SEM) image of the lanthanum-modified high-nickel ternary single-crystal cathode material in Example 1.
[0044] Figure 3 This is a transmission electron microscope (TEM) image of the high-nickel ternary single-crystal cathode material modified with lanthanum species before calcination in Example 1.
[0045] Figure 4The image shows an X-ray energy dispersive spectroscopy (EDS) image of the high-nickel ternary single-crystal cathode material modified with lanthanum species before calcination in Example 1.
[0046] Figure 5 The above are charge-discharge curves of the high-nickel ternary single-crystal cathode materials in Example 1 and the comparative example at a rate of 0.1C.
[0047] Figure 6 The cycling diagrams for the high-nickel ternary single-crystal cathode materials in Example 1 and the comparative example are shown at a 1C rate. Detailed Implementation
[0048] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0049] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0050] Example 1
[0051] (I) Preparation of cathode materials
[0052] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained; 1.986 g of single-crystal LiNi was accurately weighed. 0.83 Co 0.07 Mn 0.10 O2 (NCM) was dispersed in the above solution and stirred at 60°C for 3 hours. After centrifugation, washing and drying, the positive electrode material powder was obtained. The powder was calcined in a tube furnace at 700°C for 3 hours under an oxygen atmosphere at a heating rate of 5°C / min. After naturally cooling to room temperature, it was ground in a mortar to obtain the lanthanum-modified positive electrode material.
[0053] (II) Structural and Morphological Characterization
[0054] The crystal structure of the cathode material prepared in the examples was analyzed using a powder X-ray diffractometer (D8 Advance, Bruke). The results are as follows: Figure 1 As shown in the figure, the cathode material prepared in this embodiment conforms to the diffraction peaks of layered ternary materials and has no other impurity peaks, indicating that the material has high purity.
[0055] The morphology of the cathode materials prepared in the examples was further characterized using scanning electron microscopy (SEM-4800), and the results are as follows: Figure 2As shown in the figure, the material retains the characteristics of single-crystal LiNi after surface modification. 0.83 Co 0.07 Mn 0.10 Morphology of O2(NCM) cathode material.
[0056] The morphology of the lanthanum species-modified high-nickel ternary single-crystal cathode material before calcination was characterized using transmission electron microscopy (TEM-2100F). The results are as follows: Figure 3 As shown in the figure, the thickness of the lanthanum-containing species coating is approximately 6 nm.
[0057] Figure 4 The image shows the X-ray energy dispersive spectroscopy (EDS) analysis of the lanthanum species-modified high-nickel ternary single-crystal cathode material before calcination. The results show that a uniform and continuous lanthanum species coating layer exists on the surface of the high-nickel ternary single-crystal cathode material.
[0058] (III) Battery Assembly
[0059] The prepared 200 mg of positive electrode material was mixed with 25 mg of polyvinylidene fluoride (PVDF) binder and 25 mg of Super-P conductive agent, and approximately 200 μL of N-methylpyrrolidone (NMP) was added to prepare a slurry. Using aluminum foil as the current collector, the slurry was uniformly coated onto the aluminum foil to a thickness of 2 μm. The coating was then vacuum dried at 80 °C for 12 h to obtain the positive electrode film. A lithium metal sheet was used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) as the separator, and 1 mol / L LiPF6 (EC:DMC:DEC = 1:4:2) as the electrolyte. The cells were then assembled into a button cell in an argon-protected glove box.
[0060] (iv) Performance Testing
[0061] The assembled battery was subjected to constant current charge-discharge testing on a Blue Electric charge-discharge tester. The charge-discharge rate was 0.1C (1C = 200mA / g), and the charge-discharge range was 3.0-4.3V. The charge-discharge curve for the first cycle is shown below. Figure 5 As shown in the figure, the discharge specific capacity of this NCM cathode material can reach 197 mAh / g. The charge / discharge range is 3.0-4.3V, and the capacity retention rate after 100 cycles at 1C is 95% (e.g., ...). Figure 6 As shown in the figure, this indicates that the cathode material has good cycle stability.
[0062] Example 2
[0063] (I) Preparation of cathode materials
[0064] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 3.972 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 3 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0065] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0066] (III) Battery assembly (specific steps are the same as in Example 1).
[0067] (iv) Performance testing (the specific steps are the same as in Example 1).
[0068] Example 3
[0069] (I) Preparation of cathode materials
[0070] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 0.993 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 3 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0071] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0072] (III) Battery assembly (specific steps are the same as in Example 1).
[0073] (iv) Performance testing (the specific steps are the same as in Example 1).
[0074] Example 4
[0075] (I) Preparation of cathode materials
[0076] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 0.497 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 3 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0077] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0078] (III) Battery assembly (specific steps are the same as in Example 1).
[0079] (iv) Performance testing (the specific steps are the same as in Example 1).
[0080] Example 5
[0081] (I) Preparation of cathode materials
[0082] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 1.986 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 600℃ for 3 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0083] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0084] (III) Battery assembly (specific steps are the same as in Example 1).
[0085] (iv) Performance testing (the specific steps are the same as in Example 1).
[0086] Example 6
[0087] (I) Preparation of cathode materials
[0088] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 1.986 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 800℃ for 3 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0089] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0090] (III) Battery assembly (specific steps are the same as in Example 1).
[0091] (iv) Performance testing (the specific steps are the same as in Example 1).
[0092] Example 7
[0093] (I) Preparation of cathode materials
[0094] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 1.986 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 1 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0095] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0096] (III) Battery assembly (specific steps are the same as in Example 1).
[0097] (iv) Performance testing (the specific steps are the same as in Example 1).
[0098] Example 8
[0099] (I) Preparation of cathode materials
[0100] At 25℃, 26.4 mg of lanthanum nitrate and 26.8 mg of hexamethylenetetramine were dissolved in 30 ml of anhydrous ethanol and stirred until a clear and transparent solution was obtained. 1.986 g of single-crystal NCM was accurately weighed and dispersed in the above solution. The mixture was stirred and reacted at 60℃ for 3 h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 5 h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground with a mortar and pestle to obtain the lanthanum-modified cathode material.
[0101] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0102] (III) Battery assembly (specific steps are the same as in Example 1).
[0103] (iv) Performance testing (the specific steps are the same as in Example 1).
[0104] Comparative Example
[0105] (I) Preparation of cathode materials
[0106] At 25℃, 1.986g of single-crystal NCM was dispersed in 30ml of anhydrous ethanol solution and stirred at 60℃ for 3h. After centrifugation, washing and drying, the cathode material powder was obtained. The powder was calcined in a tube furnace at 700℃ for 5h under an oxygen atmosphere at a heating rate of 5℃ / min. After naturally cooling to room temperature, it was ground in a mortar and pestle to obtain the unmodified cathode material.
[0107] (II) Structural and morphological characterization (specific steps are the same as in Example 1).
[0108] (III) Battery assembly (specific steps are the same as in Example 1).
[0109] (iv) Performance testing (the specific steps are the same as in Example 1).
[0110] The performance test results of Examples 1-8 and the comparative batteries are shown in Table 1 below.
[0111] Table 1
[0112]
[0113]
[0114] As can be seen from the comparison of Examples 1-8 and the comparative examples, surface lanthanum modification can significantly improve the cycle stability of the cathode material, while an appropriate amount of lanthanum addition will not sacrifice its discharge specific capacity.
[0115] As can be seen from the comparison of Examples 1-4, the amount of lanthanum species coating affects the first-cycle discharge specific capacity and cycle stability of the cathode material. When the lanthanum species coating amount is too low, a sufficient stable layer cannot be formed on the surface of the ternary cathode material, thus failing to provide comprehensive protection for the cathode material surface; however, if the lanthanum species coating amount is too high, other unstable impurity phases will form on the cathode surface, leading to a decrease in the first-cycle discharge specific capacity and a deterioration in cycle stability. Even with a high lanthanum coating amount in Example 4 of this invention, the capacity retention rate after 100 cycles (89.8%) is still higher than that of the comparative example (88.3%), demonstrating that the method of improving the cycle stability of the cathode material through surface lanthanum modification in this invention is reliable.
[0116] A comparison of Examples 1 and 5-6 shows that calcination temperature affects the first-cycle discharge specific capacity and cycle stability of the cathode material. If the calcination temperature is too low, the reaction between the lanthanum coating and the solid phase on the cathode material surface is incomplete, resulting in limited improvement in the cathode material's cycle performance. However, if the calcination temperature is too high, it will damage the crystal structure of the cathode material itself and generate harmful impurities, leading to a decrease in the first-cycle discharge specific capacity. The batteries assembled from the cathode materials prepared in Examples 5 and 6 of this invention still exhibit higher capacity retention after 100 cycles than the comparative examples, demonstrating that the surface lanthanum modification method of this invention can improve the cycle stability of the cathode material.
[0117] A comparison of Examples 1 and 7-8 shows that calcination time affects the initial discharge specific capacity and cycle stability of the cathode material. Shortening the calcination time results in incomplete reaction between the electrode material and the surface lanthanum species, leading to a decrease in the initial discharge specific capacity of the cathode material and limited improvement in cycle stability. However, excessively long calcination times cause the lanthanum species coating layer to form harmful impurities on the cathode material surface, which is detrimental to improving cycle stability. The batteries assembled from the cathode materials prepared in Examples 7 and 8 still exhibit better cycle stability than the comparative examples, demonstrating the effectiveness of the surface lanthanum modification method of this invention.
[0118] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that, The method includes the following steps: (1) Dissolve the soluble lanthanum salt and precipitant in a non-aqueous solvent and stir to obtain solution A; (2) Add the high-nickel ternary cathode material to solution A and disperse it to obtain suspension B; (3) Heat suspension B, then centrifuge, wash and dry the reaction product to obtain the surface-modified high-nickel ternary cathode material; the reaction temperature is 60~80 ℃ and the reaction time is 2~6 h; (4) The surface-modified high-nickel ternary cathode material prepared in step (3) is calcined at high temperature in an oxygen atmosphere to obtain a surface-modified high-nickel ternary cathode material with lanthanum species. The calcination temperature is 600~800 ℃; the calcination time is 1~5 h; The soluble lanthanum salt is lanthanum nitrate; The precipitant is hexamethylenetetramine; The non-aqueous solvent is anhydrous ethanol; The concentration of the soluble lanthanum salt is 1×10⁻⁶. -4 ~0.01 mol / L; The concentration of the precipitant is 3 × 10⁻⁶. -4 ~0.03 mol / L; The mass ratio of the high-nickel ternary cathode material to the soluble lanthanum salt is 150~20; The cathode material includes a high-nickel ternary cathode material and a lithium lanthanate nano-modification layer formed by lanthanum modification on the surface of the high-nickel ternary cathode material.
2. The method for preparing the cathode material according to claim 1, characterized in that, In the cathode material, the mass fraction of lanthanum is 0.1-2%.
3. The method for preparing the cathode material according to claim 1, characterized in that, The high-nickel ternary cathode material has the structural formula LiNi. x Co y Mn 1-x-y O2, 0.6≤x<1, 0<y≤0.2, x+y<1.
4. The method for preparing the cathode material according to claim 3, characterized in that, The high-nickel ternary cathode material is LiNi. 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.91 Co 0.06 Mn 0.03 O2.
5. The application of the cathode material prepared by the preparation method according to any one of claims 1-4 in lithium-ion secondary batteries.
6. A lithium-ion battery, characterized in that, It contains the positive electrode material prepared by the preparation method according to any one of claims 1-4.
7. The battery as described in claim 6, characterized in that, The positive electrode of the battery also includes the conductive agent Super-P and the binder polyvinylidene fluoride (PVDF).
8. The battery as claimed in claim 7, characterized in that, In the positive electrode, the mass ratio of the positive electrode material to the conductive agent and the binder is (8~0):(1~9):1.
Citation Information
Patent Citations
Modifying method of ternary anode material
CN103456944A
Lithium ion battery positive electrode material and preparation method thereof
CN111029536A
